2m+2+3m+2m+3m+2=

Simple and best practice solution for 2m+2+3m+2m+3m+2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m+2+3m+2m+3m+2= equation:


Simplifying
2m + 2 + 3m + 2m + 3m + 2 = 0

Reorder the terms:
2 + 2 + 2m + 3m + 2m + 3m = 0

Combine like terms: 2 + 2 = 4
4 + 2m + 3m + 2m + 3m = 0

Combine like terms: 2m + 3m = 5m
4 + 5m + 2m + 3m = 0

Combine like terms: 5m + 2m = 7m
4 + 7m + 3m = 0

Combine like terms: 7m + 3m = 10m
4 + 10m = 0

Solving
4 + 10m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 10m = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 10m = 0 + -4
10m = 0 + -4

Combine like terms: 0 + -4 = -4
10m = -4

Divide each side by '10'.
m = -0.4

Simplifying
m = -0.4

See similar equations:

| 3-s+6=15 | | -6b+2b=-8 | | 5-3+6=15 | | 9.25/0.25 | | 64x=4x^3 | | 17x+8-10x=15 | | 0.2x+7=0.7x-1 | | 68/15÷63/15 | | -1/5s-1=12 | | 0.375+2m=0.625 | | -13-1/4s=7 | | x^2+4x-490=0 | | 20-2x=x+50 | | x^2-4x-490=0 | | -17-w/3=-2 | | 3x+8x-9=112 | | 0.11+2n=0.77 | | 2(x+3)=5x+9 | | 3/7(15.5) | | -(n+3)+1=-1-4n | | -6x-7=9-2x | | y*y/2 | | -0.80t+0.40=0.66 | | (8x-2)+(2x+38)+(10x-26)=180 | | 10(x-5)=9(x+9) | | 3m-40=-22 | | -84=-2-7(x+3) | | 9c(3c+5)(4c-11)=0 | | 73=f(x) | | 6x+15-2x=-25 | | log(x)2=0 | | 4/7(15.5) |

Equations solver categories